THE DIAGNOSIS OF BRAIN DISEASES USING MAGNETIC RESONANCE IMAGING TECHNIQUES - Berdiyev Behzod Shomurodovich; Djumayev Akbar Anvarovich (KONFERENSIYALAR, 2025)
Аnnotation. The function of magnetic resonance imaging in the diagnosis of neurodegenerative illnesses is reviewed in this article. The problem’s applicability and the potential of several approaches are developed. Magnetic resonance imaging techniques, both conventional and unconventional, are discussed. This review looks at contemporary MRI methods for early brain illness detection.